Nakłady na działalność badawczo-rozwojową w krajach europejskich, Stanach Zjednoczonych oraz Japonii - Piekut, Marlena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The aim of the publication was to analyze the level of expenditure on research and development activities in European countries, the United States and Japan. The publication data from Eurostat, between years 2005–2008. Two indexes, GERD and GBAORD, were used to assess the expenditure in this countries. The United States lead in spending on research and development, both as a share in GDP and in absolute terms. Among European countries, Sweden, Finland, Denmark, Germany and France spend the most on R&D. Poland holds on of the last positions. Similarly, Polish entrepreneurs invest too little in this area.